FEASIBILITY STUDY OF ABACUS TRAINING MODEL FOR IBTIDAIYAH MADRASAH TEACHERS: CASE IN BANDAR LAMPUNG - Elice, Deti; Patimah, Siti; Pahrudin, Agus; Koderi, Koderi; Fauzan, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the feasibility of the abacus skills training management model product designed to improve the competency of Madrasah Ibtidaiyah teachers. Product feasibility assessment is carried out through validation tests by design experts, material experts and language experts, practitioners and then the results are in FGD. The assessment results show that the product received a score of 78.50% from design experts in the "decent" category, 85% from material experts in the "very feasible" category, and 80% from language experts in the "very feasible" category. Overall, the average model feasibility value reached 81.2%, which is included in the "very feasible" category. These findings indicate that the abacus skills training management model has significant potential to be implemented in supporting the competency development of Madrasah Ibtidaiyah teachers. It is hoped that this model can be an innovative solution in improving the quality of learning in madrasas